(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2026)
Nearly one-third of the population reports new onset or acute insomnia in a given year, and approximately 10% endorse sleep problems consistent with diagnostic criteria for chronic insomnia. Historically, acute and chronic insomnia have been considered variations of the same condition, differentiated mainly by chronicity. The goal of this theoretical review is to summarize definitions of acute and chronic insomnia and discuss the role that hyperarousal may play in explaining differences in pathophysiology between the two forms, including the biopsychological factors that precipitate and/or perpetuate each.